Profiles of Good Teaching Practices in STEM Disciplines: An Analysis of Mixed Methods of Academic and Assessment Variables of Teaching in the First Cycle of Civil Engineering - Salvo-Garrido, Sonia; Sagner-Tapia, Johanna; Bravo-Sanzana, Mónica; Torralbo, Camila (Frontiers in Education, 2022)
A relevant area to improve the quality of undergraduate education are the STEM disciplines: science, technology, engineering, and mathematics. These disciplines have seen a drop in student interest and participation internationally. The aim of this study was to determine profiles of good teaching practices based on responses from a teaching evaluation survey and academic context variables of students in STEM disciplines using a mixed methods design. The study was conducted at a state university in southern Chile, framed in the first cycle of STEM disciplines, the Faculty of Engineering and Sciences using data from 2016 and 2017. The quantitative results revealed four groups analyzed by cluster, together with the most frequent responses according to the highest and lowest scores. The qualitative results yielded five groups of codes of greatest frequency in the twelve analysis units, which were the students’ comments divided into mathematics, physical sciences and chemistry courses. The findings suggest a need to continue developing pedagogical knowledge in STEM teachers and highlight student involvement. Actions for improvement could focus on orienting teaching skills a) with a special emphasis on pedagogical content knowledge to promote active learning; b) in the knowledge of the classroom culture and its problems associated with poor outcomes, offering the students equal opportunities of academic performance in STEM; and c) in the management of a learning environment suitable for all students, inclusive classrooms, alleviating the burden of academic success being only on students. Finally, the teaching evaluation instrument needs to be improved.